2016
DOI: 10.1123/tsp.2015-0029
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Counseling Principles and Skills to Develop Practitioner-Athlete Relationships by Practitioners Who Provide Sport Psychology Support

Abstract: 1This study examined how practitioners who provide sport psychology support use 2 counselling principles and skills to develop practitioner-athlete relationships. Semi-structured 3 interviews were conducted with thirteen competent practitioners (Mean age = 41.2 ± 10.9 4 years old, five men, eight women). Thematic analysis revealed that the participants used a 5 range of counselling principles to develop practitioner-athlete relationships including: the 6 facilitative conditions, self-disclosure, counselling sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 7 publications
2
26
0
Order By: Relevance
“…The results also support and extend existing sport psychology research (i.e., Longstaff & Gervis, 2016) which indicated that humor is a pervasive 'non-counselling' strategy used to develop and maintain the working/real alliance. Although Longstaff and Gervis (2016) did not elucidate on this strategy researchers in other contexts have previously advocated the use of humor for such purposes.…”
Section: Humor and Sport Psychology Consultancysupporting
confidence: 83%
See 2 more Smart Citations
“…The results also support and extend existing sport psychology research (i.e., Longstaff & Gervis, 2016) which indicated that humor is a pervasive 'non-counselling' strategy used to develop and maintain the working/real alliance. Although Longstaff and Gervis (2016) did not elucidate on this strategy researchers in other contexts have previously advocated the use of humor for such purposes.…”
Section: Humor and Sport Psychology Consultancysupporting
confidence: 83%
“…A preliminary investigation into the use of humor in sport psychology practice HUMOR AND SPORT PSYCHOLOGY CONSULTANCY 2 In clinical and counseling psychology interpersonal (practitioner-client) behaviors have been acknowledged as impacting positively, on client change, via the impact on the therapeutic alliance and the real relationship (Sexton & Whiston, 1994;Norcross & Lambert, 2011). Although the working alliance and real relationship in sport psychology have also been highlighted as important (e.g., Katz & Hemmings, 2009;Sharp, Hodge, & Danish, 2015) to intervention outcome (Petitpas, Giges, & Danish, 1999) there is relatively little associated research (Longstaff & Gervis, 2016;Tod & Andersen, 2012). Petitpas et al (1999) highlighted that few studies have explored service delivery in depth.…”
Section: Abstract: Working Alliance Creative Effort Humor Usementioning
confidence: 99%
See 1 more Smart Citation
“…However, the current participants used both humor styles in a positive manner. Gelso and Carter (1994) have suggested that the real relationship is the most essential element of brief therapy work, and recent research in sport (e.g., Longstaff & Gervis, 2016;Sharp et al, 2015) supports this suggestion. Gelso (2002) also argued that client-consultant relationships characterized by high levels of genuineness are likely to be most effective.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical psychology, it has been argued that the client-therapist relationship accounts for a large variance in client outcome compared to expectancy effects and therapeutic techniques (Lambert & Barley, 2001). Similarly in sport psychology, a general consensus exists that successful consultancy outcomes are influenced by the clientconsultant relationship (e.g., Longstaff & Gervis, 2016;Petitpas, Giges, & Danish, 1999;Sharp, Hodge, & Danish, 2015). For example, the working alliance (i.e., the agreement between the client and the consultant regarding shared goals, tasks, and emotional bonds; Bordin, 1979) has been suggested as an important determinant of successful consultancy outcomes.…”
mentioning
confidence: 99%